2021
DOI: 10.12750/jarb.36.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin regulates the development of caprine primordial follicles in vitro

Abstract: Kisspeptin, the product of the Kiss-1 gene, encodes a 145-amino acid peptide that is further processed to generate biologically active peptides of various lengths (10-54 amino acids). Kisspeptin was initially described to have a central role in triggering the onset of puberty, however, it has been found to be involved in all phases of reproductive life (Caraty and Franceschini, 2008). Central or peripheral administration of kisspeptin strongly induces the secretion of gonadotropins mainly via stimulation of Gn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It has been declared that kisspeptin potentiates the induction of ovarian follicle maturation and estradiol production by promoting FSH synthesis ( Hagen et al ., 2014 ; Rather et al ., 2016 ). The line with this notion, some published papers emphasized the role of this antioxidant in improving follicle development and maturity ( Taniguchi et al ., 2017 ; Magamage et al ., 2021 ). In this regard, a study revealed that the administration of kisspeptin increases the number of preovulatory follicles and raises the plasma AMH secreted by secondary follicles ( Cao et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been declared that kisspeptin potentiates the induction of ovarian follicle maturation and estradiol production by promoting FSH synthesis ( Hagen et al ., 2014 ; Rather et al ., 2016 ). The line with this notion, some published papers emphasized the role of this antioxidant in improving follicle development and maturity ( Taniguchi et al ., 2017 ; Magamage et al ., 2021 ). In this regard, a study revealed that the administration of kisspeptin increases the number of preovulatory follicles and raises the plasma AMH secreted by secondary follicles ( Cao et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%